Optimization of a Laser Ablation‐Single Collector‐Inductively Coupled Plasma‐Mass Spectrometer (Thermo Element 2) for Accurate, Precise, and Efficient Zircon U‐Th‐Pb Geochronology. (4th October 2018) - Pullen, Alex; Ibáñez‐Mejia, Mauricio; Gehrels, George E.; Giesler, Dominique; Pecha, Mark
Abstract: Many applications specific to detrital mineral U‐Th‐Pb geochronology in the Earth sciences necessitate large numbers of age observations to be made from samples and require accurate and precise isotope measurements across wide dynamic ranges in elemental concentrations and signal intensities. This implies that the laser system and mass spectrometer cannot be tuned between individual analyses as to optimize measurements based on the isotope composition and concentrations of samples and that intensity matching between the unknowns to be dated and the reference material(s) used for fractionation correction is impossible to ensure. We describe methodologies for optimization of laser ablation‐single collector‐inductively coupled plasma‐mass spectrometer for the accurate determination of initial‐Pb‐corrected (using measured 204 Pb) U‐Th‐Pb zircon ages, taking full advantage of the high sensitivity provided by the Thermo Element 2 ICP‐MS instruments fitted with a high‐performance low ultimate vacuum Jet interface. "We describe an approach that corrects for nonlinearity of the detector—the primary obstacle avoided with sample‐specific tuning—as well as element‐ and mass‐dependent fractionation and instrumental drift by using a suite of three zircon reference materials with known isotopic ratios from isotope dilution‐thermal ionization mass spectrometry measurements but with differing U and Pb concentrations." This approach allows for (experimentally) determining an instrumental fractionation versus ion beam intensity curve used for standard‐sample bracketing, thus taking into consideration an important instrumental variable that is commonly ignored in most applications of U‐Pb dating using laser ablation‐single collector‐inductively coupled plasma‐mass spectrometer. We show that these methodologies yield uncertainties and age offsets typically better than ±2.0% for individual measurements of small (e.g., 10‐μm depth × 20‐μm diameter) volumes of material. Key Points: This work describes an approach to the optimization of the Element 2 LA‐SC‐ICP‐MS for detrital zircon geochronology; the Element is currently one of the most widely used instruments for U‐Pb Nonlinearity of the secondary electron multiplier within the SC‐ICP‐MS and inaccuracy of the analog conversion factor can be partially overcome thus improving accuracy The accuracy to which Pb and U isotopes can be measured is ostensibly improved using a multiple datum approach which allows for the entire dynamic range of the secondary electron multiplier to be used